Trade strategy for rich and poor nations - Johnson, Harry G. (London : Allen and Unwin, 1971)
This study examines specific aspects of the a free trade treaty among developed countries as the next face in the liberalization of the world commerce.
Includes bibliographical references.
sju 22/01/209
Loans
Keywords: Free trade; Commercial policy; Investments, American; Developing countries